Electric motor design for steer-by-wire systems and functional safety analysis - Menekşe, Mehmet Duran; Aküner, Mustafa Caner (Journal of Mechatronics and Artificial Intelligence in Engineering, 2025)
Steer-by-Wire (SbW) systems are gaining significance in the automotive industry in response to growing demands for driving comfort and safety. By eliminating traditional mechanical steering column connections, SbW systems offer reduced power consumption and enhanced steering performance. This paper examines the design and functional safety requirements of feedback motors used in SbW systems. In SbW systems, feedback motors generate reactive torque to improve the driver’s steering feel, requiring precise control. Brushless DC (BLDC) motors are emphasized as the preferred choice due to their high reliability and efficiency. This study outlines specific parameters for the selection and design of BLDC motors and identifies suitable options. The ISO 26262 functional safety standard is crucial for ensuring the safe operation of these systems. In compliance with the ISO 26262, the failure rates of electric motors must align with the associated risk levels. Additionally, these motors should incorporate safety mechanisms capable of detecting and isolating faults. In conclusion, adherence to the ISO 26262 standards in electric motor design for SbW systems is vital for vehicle safety and performance. This paper reviews studies aimed at developing safe, efficient, and reliable motors for modern automotive applications and offers recommendations.